HEALTH MEET - MUSIC: सेहत का मीत - संगीत - Veeravani, Monisha (International Journal of Research -GRANTHAALAYAH, 2015)
Music gives people a deeper understanding on the level of sensation and motivates them to become better and this element can change the world when it is wider than our own. It is music that connects the beginning to the end and becomes the literature of our heart. Fills the soul with affection, takes the mind from deep darkness to eternal heights. Music has the status of a® God, so purity has special importance in this genre. Music is the way to cultivate the mind through the seven pure and five vocal cords. Therefore, it can be said that music is necessary to keep the body and mind healthy, cheerful. This keeps the body, mind and brain healthy, and concentrates. Stress is also removed from music. It has been proved by various scientific experiments that both music practice and yoga practice develop strength in human life and many diseases can be treated. Music therapy i.e. music therapy nowadays plays an important role in relieving many health problems. Is playing If you live under high stress or are suffering from insomnia problem, then you can take help of this therapy. Each sound produces specific waves. These sound waves directly affect our brain. Everything in existence is affected by these waves. If a music is composed with the right words and the appropriate ragas, it will work on our brain in the same way that the software works inside a computer. Since our entire body is under the control of the brain, we can get the right result by having the expected effect on the brain through remedial music. संगीत लोगों को संवेदना के स्तर पर एक गहरी समझ देकर उन्हें बेहतर बनने की दिशा में प्रेरित करता है और यही तत्व जब निज से व्यापक होता है तो दुनिया भी बदल सकती है. ये संगीत ही है जो आदि को अंत से जोडकर हमारे हृदय का साहित्य बन जाता है। आत्मा को स्नेह से भर देता है मन को गहन अन्धकार से लेकर अनन्त ऊंचाइयों तक ले जाता है । संगीत क® ईश्वर का दर्जा प्राप्त है, इसीलिए इस विधा में शुध्दता का विशेष महत्व है। सात षुघ्द अ©र पांच क®मल स्वर®ं के माध्यम से मन क® साधने का उपाय है संगीत। अतः कहा जा सकता है कि शरीर तथा मन क® स्वस्थ््ा, प्रफुल्लित रखने के लिए संगीत आवश््यक है। इससे शरीर, मन, मस्तिष्क स्वस्थ््ा रहता है, एकाग्र रहता है। संगीत से तनाव भी दूर ह®ता है। विभिन्न वैज्ञानिक प्रयोगों द्वारा यह सिद्ध हो चुका है कि संगीत साधना व योग साधना दोनों से मनुष्य के जीवन में शक्ति का विकास होता है और अनेक बीमारियों का उपचार किया जा सकता है म्यूजिक थेरेपी यानी संगीत चिकित्सा आजकल अनेक स्वास्थ्य समस्याओं से राहत दिलाने में अहम भूमिका निभा रही है। आप अगर ज्यादा तनाव में रहते हैं या अनिद्रा की समस्या से पीडित हैं तो इस चिकित्सा की सहायता ले सकते हैं । हर ध्वनि से विशिष्ट तरंगें पैदा होती हैं। ये ध्वनि तरंगें सीधे हमारे मस्तिष्क को प्रभावित करती हैं। इन्हीं तरंगों से अस्तित्व में मौजूद हर चीज प्रभावित होती है। अगर कोई संगीत सही शब्दों और उपयुक्त रागों के साथ तैयार किया जाए तो वह हमारे मस्तिष्क पर उसी तरह काम करेगा जैसे किसी ’कम्प्यूटर’ के अंदर ’साफ्टवेयर’ काम करता है। चूंकि हमारा पूरा शरीर मस्तिष्क के नियंत्रण में होता है, इसलिए हम मस्तिष्क पर उपचारी संगीत के माध्यम से अपेक्षित प्रभाव डालकर सही परिणाम प्राप्त कर सकते हैं।